Teknik Reframing untuk mengurangi pemikiran negatif pada wanita depresi dengan gejala psikotik - Niken Refanthira (Universitas Muhammadiyah Malang, 2021)
Individuals who experience depression generally have negative thoughts. The purpose of this study was to see the effectiveness of reframing to reduce negative thoughts in depression sufferers with psychotic symptoms. This research uses a qualitative case study approach with one subject. The instruments used were interviews, observations, the Beck Depression Inventory scale, World Health Organization: Disability Assessment Schedule scale, and the Standard Progressive Matrixes test. The treatment given to the subject is cognitive therapy with reframing techniques by changing the way the subject perceives the problem. The intervention was carried out with several stages with results showing that reframing was able to reframe wrong thinking and could be applied to individuals who had below-average intelligence through family assistance and a high desire to recover.